Promoting Aesthetical Values to Education - Ulvik, Marit (Frontiers in Education, 2020)
With a pressure on schools to meet the requirements of a knowledge-based global economy, human development, critical thinking and imagination seem to be given lower priority. This article argues for including the aesthetic dimension in teaching as a way to foster human development. While aesthetic subjects are cut, there is a growing interest in aesthetic methods through which students are expected to use their knowledge in new and creative ways. However, there is a tension involved in combining innovative and creative thinking with the objectives model, in which education is broken down into measurable targets. Including more than what is measurable is important to encourage students to not only copy what they are told, but to become creative and able to find their own solutions in the future. The aesthetic dimension might support independent thinking and imagination, crucial qualities in a democracy and for developing a future that we cannot yet see. Aesthetics’ is here understood in a broad sense and not limited to certain subjects. A main concern in the article is how to include aesthetics in academic subjects. Every subject has elements of emotions, intuition and interpretation and might make use of symbolic forms. The aesthetical involves knowledge that is gained through the senses and that appeals to emotions. An aesthetic approach might contribute to interest and meaning, preconditions for learning that transforms the individual. It might open up for unrealised knowledge and unexpected outcomes. Furthermore, the approach might contribute to a good life. The argumentation in the article will build on theory as well as on empirical research from upper secondary school.